Implikasies van die Grondwet vir Gesondheidsdienste - J.P. Roux (AOSIS, 1984)
The new Constitution of the RSA presents new challenges in the field of health services. For the first time the various population groups will participate in decisions about delivery of health care to their own communities. The diseases which affect the population of South Africa, however, do not have any ethnical or geographical boundaries. This necessitates effective co-ordination, despite the various authorities and services. Administrative implications include greater privatisation of functions currently performed by the authorities, devolution of power to local authorities and co-ordination regarding health personnel administration. For the allocation of finances for health services the author suggests a number of principles for the delivery of health services as well as priorities for long term spending. Management ability of health personnel at all levels in order to meet the challenges of the new Constitution is also stressed.